2023
DOI: 10.3389/fnut.2023.1251083
|View full text |Cite
|
Sign up to set email alerts
|

Evidence or no evidence for essential fatty acids in the treatment of autism spectrum disorders?

Rouzha Zlatanova Pancheva,
Silviya Nikolova,
Asena Serbezova
et al.

Abstract: Autism spectrum disorders (ASDs) are a group of neurodevelopmental disorders that affect social communication, behavior, and sensory processing, in which PUFAs are considered important. This mini-review article aims to investigate the current evidence regarding the use of essential fatty acids (EFAs) in the treatment of autism spectrum disorders (ASDs). The study examines various research studies, related to EFAs, their benefits, and their role in ASD treatment. The article focuses on exploring the potential m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…Similar conclusions were drawn in two systematic reviews by James et al [173] and Horvath et al [174]. Bozzatello et al [175], Veselinovic et al [176], and Pancheva et al [177] drew attention to the fact that clinical studies that have evaluated the effects of omega-3 FAs on the symptoms of autism are highly contrasting. According to a review by Bozzatello et al [175], four trials out of eight supported their beneficial role, whereas four did not indicate any significant clinical improvement.…”
Section: Autistic Spectrum Disorderssupporting
confidence: 53%
See 2 more Smart Citations
“…Similar conclusions were drawn in two systematic reviews by James et al [173] and Horvath et al [174]. Bozzatello et al [175], Veselinovic et al [176], and Pancheva et al [177] drew attention to the fact that clinical studies that have evaluated the effects of omega-3 FAs on the symptoms of autism are highly contrasting. According to a review by Bozzatello et al [175], four trials out of eight supported their beneficial role, whereas four did not indicate any significant clinical improvement.…”
Section: Autistic Spectrum Disorderssupporting
confidence: 53%
“…Furthermore, baseline levels of FAs in the blood are predictive factors for clinical response to omega-3 supplementation [175]. According to a review by Pancheva et al [177], 7 out of 12 trials revealed that omega-3, omega-6, and/or omega-9 FAs may have therapeutic potential in autistic spectrum disorder when administered for several weeks. Positive changes in pediatric patients were noted in relation to sleep, behavioral and verbal activity, social communication, and motivation [177].…”
Section: Autistic Spectrum Disordersmentioning
confidence: 99%
See 1 more Smart Citation